Large Scale Architectural Glass Slumping Process – Chalenges and Limitations - Andrzej Malewski; Marcin Kozłowski; Wojciech Sumelka; Marek Połedniok (Archives of Civil Engineering, 2020)
The paper focuses on the development of knowledge about the hot bending of curved architectural glass produced by the slumping process and the challenges as well as the limitations thereof. Due to the complexity of the process, many factors influence the final quality of the glass and the main objective was to better understand the procedure itself in order to improve the control and quality of the slumping process. As a result of the growing interest in this type of glass for architectural applications, the glass processing market is increasingly investing in the required technology. For the moment, this growing niche does not have a large number of direct explanations of the glass behaviour in the furnace in the available literature, which in turn encourages cooperation between the scientific community and manufacturers. This paper presents the conducted experiments that have led to a better understanding of the furnace's work and the impact of specific factors on its operation. Based on the 3D numerical model, a large sample of glass was produced, which was then scanned with a 3D laser using a method developed for the experiment. The results suggested that a more accurate test with usage of a full-size furnace is required. Based on this, the experiment was carried out using a large number of glass samples of different thicknesses. The results of the experiment helped to better understand and demonstrate the need for further research of this technology in order to optimize the quality of the process.